Solving Blasius Hybrid Nanofluid Flow Over a Permeable Plate Using the Shooting Technique - Radzuan, Mohammad Arief Haiqal; Aman, Fazlina (Enhanced Knowledge in Sciences and Technology, 2024)
The study uses a shooting technique to examine the laminar boundary layer flow of a Blasius hybrid nanofluid over a permeable plate. Using similarity transformation to transform the model from partial differential equations to ordinary differential equations using the governing equation, the study takes into consideration the effects of radiation and viscous dissipation. The solutions are then obtained by using the shooting technique with the RKF45 method in Maple software. The results indicate that there are two possible results when the plate moves in the opposite direction of the free stream. Enhanced heat transfer is also facilitated by hybrid nanoparticles and increased radiation. Hybrid nanoparticles demonstrate advantageous thermal properties resulting from synergistic effects, although these effects wane with a rise in the Eckert number. The findings elucidate that within a typical fluid without transpiration, an escalation in the parameter leads to a reduction in the skin friction coefficient and a simultaneous increase in the local Nusselt number.